Red verde para conectar el espacio público y los monumentos al paisaje urbano de Villavicencio (2023)
This project focuses on generating an urban design proposal for Villavicencio that mitigates the disconnection of green spaces, and how monuments in the city are relegated to the background when we talk about urban planning. Among the objectives are to contribute to the increase of green areas per inhabitant, to give major importance to monuments in the relationship between people and public space, and to adapt it to provide more public well-being thanks to the protection against ultraviolet radiation. For this purpose, there is going to be a constant bibliographic consultation and the analysis of information by official sources will be used to achieve a project that responds to the singularities of the territory and each of the sectors involved. Key words: Monument, cultural identity, urban renovation, landscape.